History of biochemical pregnancy was associated with the subsequent reproductive failure among women with recurrent spontaneous abortion. (April 2015) - Maesawa, Yoko; Yamada, Hideto; Deguchi, Masashi; Ebina, Yasuhiko
Abstract The aim of this study was to evaluate whether the presence of history of biochemical pregnancy (BP) was associated with clinical characteristics and the subsequent pregnancy outcome among women with recurrent spontaneous abortion (RSA). One-hundred and seventy-five RSA women with two or more clinical pregnancy losses were enrolled. The clinical characteristics were compared between 164 women with history of 0–1 BP (Group A) and 11 women with two or more BP (Group B). The frequency of previous pregnancy loss and history of in vitro fertilization and embryo transfer in Group B was higher than that in Group A; while frequency of secondary RSA in Group B was lower than Group A. The subsequent pregnancy outcome was assessed prospectively; and live-birth rate in Group A (72.9%) was higher (p < 0.05) than that in Group B (41.7%). The incidence of reproductive failure (58.3%, p < 0.05) and spontaneous abortion with normal chromosome (25.0%, p = 0.050) in Group B was higher than those (27.1 and 5.9%, respectively) in Group A. RSA women with two or more BP had higher risk of reproductive failure and spontaneous abortion with normal chromosome together with lower chance of live-birth. The results of the present study involve important information and are helpful for clinical practitioners.